ANALISIS 6 DNA REKOMBINAN DENGAN ENZIM EcoR1 - Ni Nyoman Tri Puspaningsih; Akhmaloka; Afaf Baktir; Ami Soewandi J.S.; Y. Sriwulan M. (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1997)
Amylase enzyme from Endomycopsis fibuligera capable to hidrolize starch into glucose. Insertion of amylase gene from Endomycopsis fibuligera into yeast (Saccharomyces cereviceae) will be able to increase the function of yeast (S.cereviceae) to digest more cheaper substrate, like starch. Before cloning in yeast, recombinant DNA will be made and analyzed in Escherichia coli strain DH5a. The result showed that the sixth transformant consist recombinant DNA that were sensitive to tetracycline medium. Analysis by EcoR1 digestion showed that the size of insertion fragment into Ycp 50 vector are around 0.3 untill 16 kb.